Measuring the Effectiveness of Guilt Appeals in the Promotion of Certified Products - Teah, Jun-Huan (Curtin University, 2017)
The purpose of the research aims to examine the effectiveness of anticipatory guilt appeals on Fairtrade certified products. The results show consumers’ willingness to pay more for Fairtrade certified products when aroused by anticipatory guilt. The results have also shown the importance of varying the levels of perceived inferences of manipulative intent to desired levels of guilt arousal. Self-efficacy has been shown to moderate the relationship between anticipatory guilt arousal and willingness to pay more.